Bioactive Coating Over Polymer-Ceramic Composite – An Ideal Synthetic Bone Substitute - S. BAG; S. PAL (International Journal of Pharma and Bio Sciences, 2011)
A biologically active material enables implants to bond with bone, which could significantly extend the lifetime of the artificial implants or other medical reconstructive devices. The bioactive coating adhere to the surface of the implant, binds with both implants and bone, promotes formation of hydroxyapatite and lengthens the implant lifetime. Such implants are more durable and long lasting and will promote faster healing rates and should be accessible to wider range of patients. The coating provides a surface texture onto which bone cell could be deposited or a layer of additional material onto which bone could attach. Bioactive coating can defend the prosthesis against chemical attack and also separates the prosthesis from the surrounding to avoid inflammatory or other adverse reaction by making the prosthesis biocompatible.